Mangrove Degradation in the Coastal Southeast of Nigeria: Causes, Effects and Remedies for the Future (2001)
The Nigeria Delta area of Nigeria was one of the richest regions of the country in terms of forest resources of diverse types. It is particularly endowed with the mature mangrove forests. The vegetation contained many species of unique socio-economic and ecological importance. Until very recently, the mangorve community had remained fairly secured because of the difficult terrain on which they existed. However, population pressure coupled with the agressive drive for socio-economic development from early 1970s to date have taken very serious toll on the forest resources. This has left many forest areas badly degraded or completely dereserved in some cases to the extent that the continued existence of mangrove communities in the region is under threat. This paper takes a look at the various factors responsible for mangrove forest degradation 'in the area and the effects of this on the environment. Suggestions are offered on way(s) to address the problem.